Isolation and Characterization of the Zearalenone-Degrading Strain, Bacillus spizizenii B73, Inspired by Esterase Activity - Xue Liu; Na Wu; Mingyu Zhang; Feng Xue; Qing Xu (Toxins, 2023)
Zearalenone (ZEN) is a widespread mycotoxin found in grain and feed, presenting a serious threat to animal and human health. This study investigated the ability of the novel strain B73, isolated from petroleum-contaminated soil, to detoxify ZEN. B73 was identified as Bacillus spizizenii through physiological and biochemical tests, and further confirmed based on the 16S rRNA gene sequence and the complete genome sequence. B. spizizenii B73 was capable of degrading up to 99.3% of ZEN at a concentration of 10 μg/mL in a minimal medium (pH = 7.0) within 8 h at 37 °C via HPLC-UV. In addition, B. spizizenii B73 was used to treat ZEN-contaminated wheat bran, dried distillers grains (DDGS), and corn meal, whereby the respective degradation rates reached 96.32%, 98.73%, and 80.31% after 36 h of treatment. HPLC-Q-Exactive-MS/MS analysis revealed one of the degradation products to have the formula C17H24O4. B. spizizenii B73 is a novel strain isolated from petroleum-contaminated soil, and the extracellular enzymes secreted by this strain show a remarkable ability to degrade ZEN.